2017
DOI: 10.1097/md.0000000000008341
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of remifentanil for analgesia in cesarean delivery

Abstract: Background:This study aimed to assess the efficacy and safety of remifentanil as a general anesthetic during cesarean delivery.Material and Methods:Fifty women with singleton pregnancies undergoing cesarean delivery were randomly divided into intervention and control groups, each group containing 25 subjects. Participants in the intervention group received remifentanil (infused at 2 μg/kg/h), whereas subjects in the control group were given dexmedetomidine (infused at 0.4 μg/kg/h). Outcome measurements include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Earlier infusion interruption than in previous studies (after skin incision instead of at peritoneal incision or even at delivery) should leave enough time for remifentanil redistribution and metabolism in fetal circulation, thus diminishing the probability of neonatal respiratory depression. Hemodynamic variables measured after the intubation in groups A and B were significantly lower than in group C. Therefore, both regimens attenuated cardiovascular response to endotracheal intubation, which is in accordance with previous reports [4,9,[12][13][14][15][16]. The next measurement, performed after skin incision, already showed the difference: the significant difference in SAP, DAP, MAP, and HR between groups B and C disappeared, but persisted in A compared to C. At the time of peritoneal incision and at the delivery measured hemodynamic variables were significantly lower in group A compared to both C and B group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Earlier infusion interruption than in previous studies (after skin incision instead of at peritoneal incision or even at delivery) should leave enough time for remifentanil redistribution and metabolism in fetal circulation, thus diminishing the probability of neonatal respiratory depression. Hemodynamic variables measured after the intubation in groups A and B were significantly lower than in group C. Therefore, both regimens attenuated cardiovascular response to endotracheal intubation, which is in accordance with previous reports [4,9,[12][13][14][15][16]. The next measurement, performed after skin incision, already showed the difference: the significant difference in SAP, DAP, MAP, and HR between groups B and C disappeared, but persisted in A compared to C. At the time of peritoneal incision and at the delivery measured hemodynamic variables were significantly lower in group A compared to both C and B group.…”
Section: Discussionsupporting
confidence: 92%
“…In studies reporting the use of remifentanil during the I-D period dosing regimens were different; hemodynamic stability was often achieved at the expense of neonatal respiratory depression [2,4,[6][7][8][9][11][12][13][14][15][16]. In the present study, we investigated the effects of two remifentanil dosing regimens, used during the I-D period, on maternal hemodynamics and neonatal outcome in attempt to find the best compromise between the attenuation of maternal stress response and avoidance of neonatal adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies with 210 patients reported blood pH values for the umbilical artery and vein 28,30–32 . The combined results showed no evidence of a difference between the remifentanil (7.30; 95% CI, 7.26 to 7.34) and dexmedetomidine (7.30; 95% CI, 7.27 to 7.33) groups for pH values of the umbilical arterial blood: WMD: 0.00; −0.02 to 0.02; τ 2 = 0.00 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In all the studies included in this review, dexmedetomidine and remifentanil were given via continuous infusion. In four studies, both drugs were given as a bolus followed by a continuous infusion, 28,29,31,32 and in one study, the drugs were administered using continuous infusion alone 30 . However, some other studies, not in our review, used a single bolus dose without continuous infusion 39–43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation